KONTRIBUSI MOTIVASI MENGAJAR DAN KECERDASAN EMOSIONAL DALAM PENGGUNAAN METODE CERAMAH GURU MADRASAH TSANAWIYAH - Syahraini Tambak; Desi Sukenti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Emotional intelligence and teaching motivation contribute to developing teacher success using the lecture method. This research is very significant in exploring how the contribution of emotional intelligence and teaching motivation to the success of teachers in using the lecture method at Madrasah Tsanawiyah. This type of research is a correlation that aims to examine the effect of emotional intelligence and teacher motivation to use the lecture method. The subjects of this study were teachers of the field of Fiqh, al-Qur'an, Hadith, Morals, Islamic Cultural History, and Arabic, with a total population of 126 people and were studied in general. The questionnaire was used as a data collection technique and analyzed using the Multiple Linear Regression Test technique. It is produced that teachers who possess and master emotional intelligence and motivation to teach are able to build and develop the ability of teachers to use the lecture method in the learning process in madrasas.